A case–control study of farming and prostate cancer in African-American and Caucasian men. Issue 3 (15th August 2006) - Meyer, Tamra E; Coker, Ann L; Sanderson, Maureen; Symanski, Elaine
Abstract : Objective: To determine the risk of prostate cancer associated with farming by duration, recency and specific activities among African-Americans and Caucasians. Methods: This population-based case–control study had information on farming-related activities for 405 incident prostate cancer cases and 392 controls matched for age, race and region in South Carolina, USA, from 1999 to 2001. Cases with histologically confirmed, primary invasive prostate cancer who were aged between 65 and 79 years were ascertained through the South Carolina Central Cancer Registry. Appropriately matched controls were identified from the Health Care Financing Administration Medicare Beneficiary File. Data were collected using computer-assisted telephone interviewing, and adjusted odds ratios (aOR) were estimated using unconditional logistic regression. Results: Farming was associated with increased risk of prostate cancer in Caucasians (aOR 1.8; 95% confidence interval (CI) 1.3 to 2.7) but not in African-Americans (aOR 1.0; 95% CI 0.6 to 1.6). Regarding specific farming activities, farmers who mixed or applied pesticides had a higher risk of prostate cancer (aOR 1.6; 95% CI 1.2 to 2.2). Increased risk of prostate cancer was observed only for those farming <5 years. Conclusions: Increased risk of prostate cancer for farmers in this study may be attributable to pesticide exposure. Racial differences in the association between farming and prostate cancer may be explained by different farming activities or different gene–environment interactions by race.